History outside the classroom : the use of museums in the teaching of history - Rheeder, Willem Lodewikus (Rhodes University, Faculty of Education, Department of Education, 1988)
In the modern technical age in which we live , knowledge of the past is often pushed into the background As a result of this history teaching often becomes an attempt to pump an assortment of arbitrary facts into the minds of scholars by means of 'chalk and talk' methods. Educationists all over the world see this tendency as the major reason for the declining popularity of history as a school subject . In other parts of the world, such as the United States of America and Britain, education departments and teachers have faced this challenge and it seems as if the status of history as a school subject has been retrieved . In the Republic of South Africa the new core syllabuses are geared towards moving away from the earlier restricted emphasis of facts, but there is very little guidance on how teachers are to implement this 'new' approach, which focus more on the "how" of history and on the teaching of historical skills In this thesis museum visits as one of the modes of outdoor education, is studied as a possible additional alternative method of teaching history in South African schools . A study is made of what museums are and of the possible educational values of museum visits. It soon becomes clear that the major beneficial aspect of museum visits could be the acquisition of historical skills such as comprehension, application , analysis , synthesis and evaluation In order to gain insight into the practical implementation of museum visits several groups were observed while visiting the museum, after which two pilot studies were undertaken in the Kaffrarian and South African Missionary Museums with Black standard ten pupils and senior student teachers . Attention is given to aspects of administrative , teacher and pupil preparation the implementation of the visit and the types of follow-up work which could be used. During and after the implementation of the two pilot studies certain characteristic problems were experienced these are : the compilation of worksheets and cultural differences . The most important of language difficulties : It also became clear that education officers at museums find it difficult to cope with the special educational needs of the different visiting groups . For this reason an approach is advocated where the teacher compiles his own worksheet suited to the needs of his specific pupils Guidelines are given as to how pre-planned worksheets could be adapted : how different question-types could be used to compile a worksheet in which skills ascend from the simple to the complex: and how worksheets could be compiled for mixed ability groups. It is hoped that this thesis will lead to renewed interest in the use of the museum in the teaching of history and will serve as guideline for teachers planning to take history "out of its coffin".
Keywords: Uncatalogued